2006
DOI: 10.3200/jach.55.1.17-26
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Risk Factors for Suicidal Thoughts at a Nontraditional Commuter School

Abstract: The sample of students completing the National College Health Assessment (NCHA) Survey at the University of Utah differs from the national reference group for the NCHA 2003 in age, employment, residence, and marital status. The purpose of this study is to determine if the defining characteristics of a commuter school increase the risk for suicidal thoughts. During the fall semester of 2004, the University of Utah implemented a randomized electronic survey assessing the student body's health status in several a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…This is in agreement with previous study findings. 30,[33][34][35][36] This could be linked with the fact that students live off-campus were responsible to pay monthly house rent, prepare or buy daily meals and deal any issues raised related to the house or apartment they live in. 15 There is also evidences that living alone is the risk factor for stress and anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…This is in agreement with previous study findings. 30,[33][34][35][36] This could be linked with the fact that students live off-campus were responsible to pay monthly house rent, prepare or buy daily meals and deal any issues raised related to the house or apartment they live in. 15 There is also evidences that living alone is the risk factor for stress and anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, while college student samples are often used to test specific theory-driven hypotheses on STB (e.g., 11,12 ), there is a lack in understanding of how STB is concentrated in student populations according to basic correlates. Previous studies have suggested that basic correlates may include socio-demographic (e.g., gender 13 , age 14 , socio-economic status 15 , religion 16 , sexual orientation 17 ) as well as college-related variables (e.g., living situation 13 , student job 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…40 A study of American students attending a non-traditional commuter college suggested that serious suicidal ideation was associated with living off campus, being gay or bisexual, and having a history of emotional abuse, assault, and unwanted sexual contact. 41 Suicidal ideation among American undergraduate university students has also been significantly negatively associated with positive health attitudes, and positively associated with depression, drug use problems, sleep problems, and with being overweight. 42 Arria et al 2 have suggested that suicidal ideation among university students may have a unique aetiology because of the challenges associated with their developmental period.…”
Section: Introductionmentioning
confidence: 99%